Sharia Law construction regarding early name change of Ijarah object: A case study of Wakalah in Sharia banking practice - Madani, Farid; Mukhlas, Oyo Sunaryo; Nurhikmah, Aulia (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2025)
This article critically examines the issue of premature ownership transfer (early name change) in Ijarah Muntahiya Bittamlik (IMBT) contracts within Indonesian Islamic banking, focusing on both sharia and national legal perspectives. Premature transfer is understood as the transfer of ownership before the lease period ends, which raises concerns of legal certainty, potential tadlīs (disguised contract), and elements of gharar (uncertainty). Using a qualitative juridical-empirical approach, this study analyzes DSN-MUI fatwas, national legal regulations, and operational practices of Islamic banks. The findings reveal that premature ownership transfer contradicts both sharia principles and positive law, as it undermines fiduciary guarantees and weakens consumer protection. The main challenge identified is the persistence of such practices in the field due to administrative efficiency, often at the expense of normative compliance. As an alternative, the study recommends the implementation of the wakalah scheme, whereby dealers authorize banks to process ownership transfer only after all lessee obligations have been fulfilled, thus ensuring both compliance and efficiency. Contribution: This study contributes to the development of Islamic economic law by integrating classical fiqh, national regulations, and contemporary practices, while also offering practical recommendations for the Islamic banking industry to strengthen legal certainty, consumer protection, and global competitiveness.